All Days 2009
DOI: 10.2118/126627-ms
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Enhanced Coalbed Methane and Storage: Is There Promise?

Abstract: Since the early 1980s, engineers and geologists have been unlocking the secrets of coal seam gas reservoirs. With time and technology advances, such as multi-lateral horizontal drilling, these reservoirs have contributed mightily to the Nation's gas supply. Many of these prolific reservoirs are maturing and field operators now look to improve incremental recoveries from these natural gas sources. One such method is through the use of carbon dioxide enhanced coalbed methane (CO 2 -ECBM).CO 2 -ECBM is a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Potential subsurface CO 2 disposal and storage candidates include depleted oil and gas reservoirs (Krumhansl, et al, 2002;Le Gallo et al, 2002;Oldenburg and Benson, 2002;House, et al 2003;Seo and Mamora, 2003;Pawar, et al 2004;Sobers et al, 2004;Barrufet et al, 2010;and Oldenburg and Doughty, 2010 ); coalbed methane and shale gas reservoirs (Plug, et al, 2008;Jikich, et al, 2009;Koperna and Riestenberg, 2009;and Schepers, et al, 2009); and deep saline or brackish aquifers (Pruess et al, 2001;Kumar et al, 2005;Ozah et al, 2005;Izgec et al, 2008;Nghiem et al, 2009;Fang et al;and Han et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Potential subsurface CO 2 disposal and storage candidates include depleted oil and gas reservoirs (Krumhansl, et al, 2002;Le Gallo et al, 2002;Oldenburg and Benson, 2002;House, et al 2003;Seo and Mamora, 2003;Pawar, et al 2004;Sobers et al, 2004;Barrufet et al, 2010;and Oldenburg and Doughty, 2010 ); coalbed methane and shale gas reservoirs (Plug, et al, 2008;Jikich, et al, 2009;Koperna and Riestenberg, 2009;and Schepers, et al, 2009); and deep saline or brackish aquifers (Pruess et al, 2001;Kumar et al, 2005;Ozah et al, 2005;Izgec et al, 2008;Nghiem et al, 2009;Fang et al;and Han et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At present, several geological CO 2 sequestration technologies, such as CO 2 injection into saline aquifer, CO 2 -EOR, CO 2 -ECBM, and so forth, have been studied to minimize the CO 2 release into the atmosphere, and these projects have been operating all over the world [1][2][3][4][5][6]. Studies have shown that unmineable coal seams (seams too deep or too thin to be mined economically) are pretty attractive as one of the promising options for CO 2 sequestration because of their large CO 2 sequestration capacity, long time CO 2 trapping, and extra enhanced coalbed methane (ECBM) production bene�ts [1,[7][8][9][10]. Field experience with CO 2 injection into coal seam is limited, although �eld tests are planned or are being conducted in the USA, Canada, Poland, Australia, and Japan [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was often believed that the desorbed gas in matrix pores moved to cleats driven by concentration difference in molecular diffusion form (Cervi, 1967;Smith and Williams, 1984;King, 1985;Gray, 1987a;Gray, 1987b;Ertekin and Sung, 1989;Kolesar et al, 1990;Anbarici and Ertekin, 1990;Harpalani et al 1991;Zhou and Lin, 1992;Saulsberry et al, 1996;Kong, 1999;Reeves and Pekot, 2001;Fu et al, 2003;Shi and Durucan, 2003;Shi and Durucan, 2008;Hossein, 2006;Koperna and Riestenberg, 2009). The common diffusion models included: (1) pseudo steady-state diffusion model, in which it was assumed that the moving process of desorbed gas from matrix pores to cleats followed the Fick's first law and there was an average gas concentration in each matrix block unit.…”
Section: Introductionmentioning
confidence: 99%